Legal and Institutional Frameworks for DPRD-Led Post-Disaster Recovery in Urban and Regency Areas - Muhammad Yopie Aulia Insan Nasution; Rahmat Ramadhani (Abdurrauf Social Science, 2026)
This study examines the legal and institutional authority of the Regional People's Representative Council (DPRD) in post-disaster rehabilitation policies at the district and city level. The research focuses on the DPRD’s legislative, budgetary, and oversight functions as mandated by Law Number 23 of 2014 concerning Regional Government and Law Number 17 of 2014 concerning MPR, DPR, DPD, and DPRD. Findings indicate that the DPRD possesses both legal and political legitimacy to influence the formulation and implementation of post-disaster rehabilitation policies, positioning it as a key actor in ensuring that reconstruction efforts address not only physical infrastructure but also fundamental community rights, such as housing, health, education, and sustainable livelihoods. However, the study reveals that the practical exercise of DPRD authority remains limited. Its functions tend to be procedural and formalistic, with insufficient alignment between budget allocations, legislation, and the actual needs of disaster-affected communities. Limited community participation in policymaking further contributes to a gap between intended policies and outcomes. The study suggests that strengthening the DPRD’s role requires a shift toward proactive and substantive engagement, including the development of region-specific post-disaster regulations, enhanced oversight mechanisms, and participatory approaches that involve affected communities. Optimizing these functions would allow the DPRD to ensure more effective, inclusive, and sustainable post-disaster rehabilitation governance.